Antidiarrheal and antispasmodic activities of Vincetoxicum stocksii are mediated through calcium channel blockade - Abdul Jabbar Shah; Mudassar A. Zaidi; Hassan Sajjad; . Hamidullah; Anwarul-Hassan Gilani (Bangladesh Pharmacological Society, 2011)
This study was carried out to explore the mechanism underlying antidiarrheal and antispasmodic activities of Vincetoxicum stocksii. The crude extract of V. stocksii provided 12-24% protection from castor oil-induced diarrhea at the dose of 300-1,000 mg/kg, similar to loperamide. In isolated rabbit jejunum preparations, V. stocksii  caused inhibition of the spontaneous and high K+ (80 mM)-induced contractions, with respective EC50 values of 2.53 (1.65-3.90) and 0.95 mg/mL (0.63-1.42), similar to that caused by verapamil, suggesting the calcium channel blocking  effect. Loperamide caused inhibition of spontaneous and high K+-induced contraction, with respective EC50 values of 8.59 (6.33-10.11) and 9.12 µM (7.33-12.81). The calcium channel blocking activity was further confirmed when pretreatment of the tissues with V. stocksii  (1-3 mg/mL) caused a rightward displacement of the Ca++ concentrations response curves, similar to that produced by verapamil; constructed in Ca++ free medium. These data indicate that the crude extract of V. stocksii contains calcium channel blocking constituents that may possibly explain its medicinal use in hyperactive states of gut, such as, diarrhea and spasms.